If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(0) + 3y = 12 Multiply 6 * 0 0 + 3y = 12 Anything times zero is zero. 0 + 3y = 12 Remove the zero: 3y = 12 Solving 3y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = 4 Simplifying y = 4
| X+70+x+124=180 | | 5.2e=46.8 | | 1/236-1/9x | | X+17+x+124=180 | | 12.94=d-55.2 | | 3(u-2)= | | 27+x=100 | | 2x^4-x^3+9x^2-4x+4=0 | | 42.4=c+27.9 | | -42x^2-19x=0 | | ln(x+2)=2ln(x) | | 3/5d=-12 | | -5y+2(0)=-10 | | x^3-4x^2-20=-48 | | 15=12(5x+8) | | -4(m-2)=6m+5 | | Ab+c=b | | -114+7x=-2x+147 | | (v/8)-9=-13 | | -1/3-21/3 | | 5t(3-6t)= | | (v/8 | | X^3-2x=100 | | 35x^2-34x+8=0 | | 34=-2-x^2 | | 2w(4+3w)= | | 3+11=-2(6x-7) | | y(-5/3)=1 | | -5(0)+2x=-10 | | 9=38(3x+32) | | 5x-3=40x+4 | | 9 = 38(3x+32) |